OPTIMIZATION AND VALIDATION OF A LIQUID CHROMATOGRAPHIC METHOD FOR DETERMINATION OF CAPSAICIN IN CHILI PEPPERS - Pavón-Pérez, Jessy; Peña-Farfal, Carlos; Aranda, Mario; Henriquez-Aedo, Karem (Journal of the Chilean Chemical Society, 2019)
Capsaicinoids are organic compounds present in several foods like chili peppers. This group of molecules are responsible of fruit pungency, as well as, of several healthy properties. The present work reports an optimized and validated liquid chromatography method coupled to fluorescence and mass spectrometry detectors for a selective determination of capsaicin in Chili peppers (Capsicum annum and C. pendulum). To the best our knowledge this is the first report about capsaicin determination in chili peppers commercialized in Chile. Chromatographic conditions were optimized giving the following optimal conditions: 76% organic phase (MeOH: ACN: acetic acid (50:50:0.1 v/v/v) at 9 min of gradient program and column temperature of 35°C. With these conditions capsaicin, dihydrocapsaicin and nordihydrocapsaicin were separated in 15 min. Data calibration curve (0.01-2.00 mg L-1) fitted a linear regression model with a determination coefficient (R2) of 0.9986. Repeatability (relative standard deviation, RSD) and intermediate precision (RSD) showed values of 1.51% (n=6) and 1.04% (n=3), respectively. Recovery (n=3) at three levels ranged from 94.80 to 109.40%, (RDS <2.39%). The method was applied to analyze 10 chili peppers varieties commercialized in Chile. A broad range of capsaicin and dihydrocapsaicin contents were observed, finding values from 0.1 up to 127.3 μg g-1.